Adaptation and piloting of an integrated intervention model for alcohol use disorders in primary healthcare in rural Tanzania: a study protocol. Issue 10 (31st October 2020) - Mushi, Dorothy Peter; Hanlon, Charlotte; Francis, Joel Msafiri; Teferra, Solomon
Abstract : Introduction: Integration of evidence-based interventions for alcohol use disorders (AUDs) into primary healthcare has potential to increase coverage and reduce population burden. However, these interventions are rarely implemented in low- and middle-income countries and there is little existing guidance on how this could be achieved. The aim of the proposed study is to adapt and pilot an integrated model for AUDs in Tanzanian primary healthcare. Methods and analysis: The study design will include a situational analysis, a qualitative study, a series of participatory Theory of Change (ToC) workshops and pilot intervention study. The evidence-based packages of care for AUD from the WHO mental health Gap Intervention Guide will form the basis of intervention. The situation analysis will use publicly available data to identify existing resources and system functioning. In-depth interviews will be conducted with key stakeholders (people with lived experience of substance use problems, health workers, health planners and community-based organisations) to identify barriers and facilitators to integration and recommended implementation strategies. Thematic analysis will be used. Triangulation of findings will inform the ToC map for the adapted model of integrated services for AUDs. This model will then be piloted. Change in knowledge, skills and attitudes of health workers will be measured pre-implementation and post-implementation. Interrupted time series analysis will be used to identify change in the rate of identification of AUDs beyond that observed due to secular trends or by chance. The integrated model will be finalised for future implementation and larger-scale evaluation. Ethics and dissemination: Ethical approval was obtained from Addis Ababa University College of Health Science Institutional Review Board and Muhimbili University of Health and Allied Sciences Institutional Review Board. Findings will be disseminated to inform strategies for scale up of integrated interventions for people with AUDs in Tanzania and similar contexts.